2022
DOI: 10.1177/22799036221124054
|View full text |Cite
|
Sign up to set email alerts
|

A literature analysis of scientific research on gender incongruence in Muslim nations

Abstract: This study aims to chart and review the unexplored transgender research portfolio of Muslim countries using bibliometric method. Data retrieved from the Scopus database were analyzed using CiteSpace, VOSviewer, Biblioshiny, and ScientoPy software. It was found that barring Turkey and Iran, transgender research has been minimal in most Muslim countries. The collective productivity is gradually but surely rising. Around 84% of the publications have been collaborative efforts. The keyword analysis revealed that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Furthermore, in another bibliometric study , Arnull et al (2021) found patterns and gaps in the sexual and reproductive health of transgender people, suggesting a comprehensive study and understanding of the rights of transgender people. However, in contexts where this condition is still not tolerated, as is the case in the Muslim scenario (Taslim et al, 2022), there is a great need for transgender research to raise general awareness, as in scenarios such as this there is still a need to resolve disputes about gender dysphoria..…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in another bibliometric study , Arnull et al (2021) found patterns and gaps in the sexual and reproductive health of transgender people, suggesting a comprehensive study and understanding of the rights of transgender people. However, in contexts where this condition is still not tolerated, as is the case in the Muslim scenario (Taslim et al, 2022), there is a great need for transgender research to raise general awareness, as in scenarios such as this there is still a need to resolve disputes about gender dysphoria..…”
Section: Introductionmentioning
confidence: 99%